Co-immunoprecipitation assay using endogenous nuclear proteins from cells cultured under hypoxic conditions - Zheng, Xiaofeng (2020)
Low oxygen levels (hypoxia) trigger a variety of adaptive responses with the Hypoxia-inducible factor 1 (HIF-1) complex acting as a master regulator. HIF-1 consists of a heterodimeric oxygen-regulated α subunit (HIF-1α) and constitutively expressed β subunit (HIF-1β) also known as aryl hydrocarbon receptor nuclear translocator (ARNT), regulating genes involved in diverse processes including angiogenesis, erythropoiesis and glycolysis. The identification of HIF-1 interacting proteins is key to the understanding of the hypoxia signaling pathway. Besides the regulation of HIF-1α stability, hypoxia also triggers the nuclear translocation of many transcription factors including HIF-1α and ARNT. Notably, most of the current methods used to study such protein-protein interactions (PPIs) are based on systems where protein levels are artificially increased through protein overexpression. Protein overexpression often leads to non-physiological results arising from temporal and spatial artifacts. Here we describe a modified co-immunoprecipitation protocol following hypoxia treatment using endogenous nuclear proteins, and as a proof of concept, to show the interaction between HIF-1α and ARNT. In this protocol, the hypoxic cells were harvested under hypoxic conditions and the Dulbecco's Phosphate-Buffered Saline (DPBS) wash buffer was also pre-equilibrated to hypoxic conditions before usage to mitigate protein degradation or protein complex dissociation during reoxygenation. In addition, the nuclear fractions were subsequently extracted to concentrate and stabilize endogenous nuclear proteins and avoid possible spurious results often seen during protein overexpression. This protocol can be used to demonstrate endogenous and native interactions between transcription factors and transcriptional co-regulators under hypoxic conditions.